The Hermeneutic Study in Jambi Malay Phrases as a Local Genius Culture - Rengki Afria; Warni (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2020)
This study aims to inventory, document, describe, and analyze the form, types, functions, and meanings of Jambi Malay Traditional Phrases: Hermeneutic Studies. The method used is a qualitative descriptive method. The data source is in the form of traditional Jambi Malay expressions. The data of this research are proverbs, petitih, kias, proverbs in Jambi Malay. The results of the study concluded that some data on Jambi's traditional Malay expressions, in the form, kind, and meaning of proverbs.. In general, the Jambi Malay community is not open in their speech, so they use figures of speech to convey the message in the speech. Jambi Malay traditional expressions have a function in social life in the community. These functions are: As a means of community education, As advice, and As a cultural treasure of oral tradition Keywords: expressions, traditional, Jambi Malay, hermeneutic